Le concile de Charroux (989) et les coutumes du comté de la Marche: A la recherche des mécanismes de reglement de conflits - Gergen, Thomas (Journal on European History of Law, 2019)
The article builts up the link between the Council of Peace from Charroux in 989 and the customary law that applied in situ in the 12th and 13th centuries. Moreover, it intents to furnish the proof of an organic increase of law at that time. Public and ecclesiastical law were living together, side by side, without any separation in the medieval legal world, above all in a « France without government » (P. Geary).